Estratégia terapêutica na doença venosa crónica - Medeiros, J; Mansilha, A (My University, 2012)
Chronic venous disease (CVD) is a highly prevalent pathology that compromises patient’s quality of life, and has an important impact socioeconomically. Its treatment passes through the adoption of hygiene-dietetic measures, pharmacological therapy and elastic compression, as well as approaches that are able to ablate venous reflux and hypertension such as mechanical, thermic or chemical ablations. Due to the multiplicity of therapeutic approaches available nowadays, it is important to search for the more effective ones. The objective of this work is to establish a systematic clinical orientation for patients with chronic venous disease, taking into account the CEAP classification, the published results and the recommendations available, in a way to achieve clinical improvement and to answer patient’s expectations. English articles were searched in Medline in concern to the treatment of chronic venous disease. Articles cited by others contained in the initial research were also included. It was possible to understand that chronic venous disease treatment must be individualized and established according to the clinical state. Hygiene-dietetic measures must be adopted by all patients and the different compressions degrees adjusted to the CEAP classification. Pharmacological therapy induces symptomatic relieve and improves complications. All ablation techniques can be performed in an ambulatory setting. Thermal ablation is a promising treatment although there is lack of long term results for recurrence, whereas the chemical ablation, despite being the cheapest, is the mayor cause of pigmentation and recanalization. Mechanical approaches can be performed without general anesthesia and patients are able to return to work the day after the procedure.
Therapeutic strategy in the chronic venous disease
Keywords: Venous Insufficiency; Insuficiência Venosa